2008
DOI: 10.1597/06-171.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cleft Palate Repair on the Susceptibility to Contraction-Induced Injury of Single Permeabilized Muscle Fibers from Congenitally-Clefted Goat Palates

Abstract: Objective-Despite cleft palate repair, velopharyngeal competence is not achieved in ~15% of patients, often necessitating secondary surgical correction. Velopharyngeal competence postrepair may require the conversion of levator veli palatini muscle fibers from injury-susceptible type 2 fibers to injury-resistant type 1 fibers. As an initial step to determining the validity of this theory, we tested the hypothesis that, in most cases, repair induces the transformation to type 1 fibers, thus diminishing suscepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…In contrast, cleft muscles contain a higher proportion of fast fibers and also a reduced capillary supply compared with normal soft palate muscles [29][30][31] . Fast fibers are more prone to contraction-induced injury [31][32][33] . The accompanying poor capillary supply may also promote fibrosis 34,35 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, cleft muscles contain a higher proportion of fast fibers and also a reduced capillary supply compared with normal soft palate muscles [29][30][31] . Fast fibers are more prone to contraction-induced injury [31][32][33] . The accompanying poor capillary supply may also promote fibrosis 34,35 .…”
Section: Introductionmentioning
confidence: 99%
“…The hearing level returns to normal at an average of 6 years after the operation, and the longest noted delay was 17 years. An animal study conducted by Rader et al (2008) demonstrated that the palate muscle fiber may exhibit adaptive alterations after palatoplasty, that is, type II muscle fibers transformed into type I after surgery and gradually form a normal distribution of muscle fiber types, which benefits speech and hearing restorations.…”
Section: Discussionmentioning
confidence: 99%
“…25 Further, fast fibers are more prone to contraction-induced injury. 24,26,27 Muscle Regeneration in the Soft Palate…”
Section: Tissue Engineering For the Soft Palatementioning
confidence: 99%